Enhancing Scientific Reporting Skills and Learning Outcomes through SAVI-Based Practical Work - Sarjana, Moh; Maknun, Djohar; Maryuningsih, Yuyun (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
Learning outcomes and scientific reporting skills are key components that need improvement in laboratory-based learning. This study aims to test the application of the SAVI approach in a laboratory-based learning context to students' scientific reporting skills. The method used is a quasi-experimental design for SAVI-based practicum activities. The assessment of scientific reporting skills uses an instrument to evaluate practicum reports. Learning outcomes are measured using multiple-choice questions. Data analysis uses N-Gian and t-test. The results show that the scientific reporting skills of experimental class students with an average of 81.81 are higher than the control class 73.61, but the difference is not significant (p > 0.05); the increase in student learning outcomes is significantly different (p < 0.05), with an N-gain of 0.57 (moderate) for the experimental class and 0.26 (low) for the control class. The SAVI approach has been proven effective in improving learning outcomes and scientific reporting activities, although students' physiological and psychological barriers still need to be further addressed in its application.